Cohort study of endodontic therapy success - Travassos Rosana Maria Coelho; Caldas Junior Arnaldo de França; Albuquerque Diana Santana de (Fundação Odontológica de Ribeirão Preto, 2003)
A retrospective cohort study was carried out aiming to assess the success rate of endodontic treatment of patients from the Faculty of Dentistry, University of Pernambuco, Brazil. The dental records of the sampling comprised all patients treated in 1998 and 1999. Trials were standardized and a pilot study was carried out to determine the feasibility of the proposed study. Chi-square and Fisher's exact tests were used to calculate the level of significance that was set at 5%. Logistic regression models were used to confirm significant effect of some variables on the endodontic outcome. The final sample size comprised 311 (75.9%) women and 99 (21.1%) men. The majority of cases (82.9%) were considered successful. Success was less frequent for patients with up to primary school education (55.6%) than for those with a higher degree of education (89.7%). The vital condition of the pulp showed a statistically significant relationship with the success of endodontic therapy (p<0.05). These results suggest that it is possible to attain very high success rates for endodontic treatment when both the intraradicular and the extraradicular causes of failure of endodontic treatment are well managed.